The complete mitochondrial genome of Eriocheir japonica sinensis (Decapoda: Varunidae) and its phylogenetic analysis. (October 2015) - Liu, Qiu-Ning; Zhang, Hua-Bin; Jiang, Sen-Hao; Xuan, Fu-Jun; Li, Chao-Feng; Zhang, Dai-Zhen; Zhou, Chun-Lin; Tang, Bo-Ping
Abstract: The complete mitochondrial genome (mitogenome) can provide novel insights into understanding the mechanisms underlying mitogenome evolution. In this study, the complete mitogenome of Eriocheir japonica sinensis (Decapoda: Varunidae) was determined to be 16, 378 bp, including 13 protein-coding genes (PCGs), two rRNA genes, 22 tRNA genes and a D-loop region. The AT skew of the E. j. sinensis mitogenome was slightly negative (−0.016), indicating a higher number of T compared with A nucleotides. The nucleotide composition of the mitogenome was also biased toward A + T nucleotides (71.6%). All PCGs were initiated by ATN codons. Eight of the 13 PCGs harbored the incomplete termination codon by T, or TA. All other tRNA genes displayed a typical clover-leaf structure of mitochondrial tRNA. The D-loop region of the E. j. sinensis mitogenome was 918 bp in length. Based on 13 PCGs, phylogenetic analysis confirmed the placement of E. j. sinensis within the Varunidae. Highlights: The complete mitochondrial genome of Eriocheir japonica sinensis was determined. This mitochondrial genome has the typical gene organization and order of Eriocheir mitogenomes. E . j . sinensis has a close evolutionary relationship with the crabs in Varunidae.